Connections of the superior colliculus to shoulder muscles of the rat: a dual tracing study - Johanna M Rubelowski; Marion eMenge; Claudia eDistler; Markus eRothermel; Klaus-Peter eHoffmann (Frontiers Media S.A., 2013)
AbstractPrevious investigations indicate that the superior colliculus (SC) is involved in the initiation and execution of forelimb movements. In the present study we investigated the tectofugal, in particular the tecto-reticulo-spinal projections to the shoulder and arm muscles in the rat. We simultaneously retrogradely labelled the premotor neurons in the brainstem by injection of the pseudorabies virus PrV Bartha 614 into the m. rhomboideus minor and m. acromiodeltoideus, and anterogradely visualized the tectofugal projections by intracollicular injection of the tracer FITC dextrane. Our results demonstrate that the connection of the SC to the skeletal muscles of the forelimb is at least trisynaptic. This was confirmed by long survival times after virus injections into the muscles (98-101h) after which numerous neurons in the deep layers of the SC were labelled. Transsynaptically retrogradely labelled brainstem neurons connected disynaptically to the injected muscles with adjacent tectal terminals were predominantly located in the gigantocellular nuclear complex of the reticular formation. In addition, putative relay neurons were found in the caudal part of the pontine reticular nucleus. Both tectal projections to the nucleus gigantocellularis and the pontine reticular nucleus were bilateral but ipsilaterally biased. We suggest this projection to be involved in more global functions in motivated behaviour like general arousal allowing fast voluntary motor activity.